Números inteiros, congruências e somas de quadrados - Lima Júnior, Gustavo Oliveira (2013)
This paper proposes a way of presenting to primary pupils some concepts associated with the set of integers such as divisibility, GCD, LCM, congruences and sums of squa-res in a more pragmatic and less abstract way. Presenting them through visual forms or contextualized problems with our physical reality more immediate, favoring a better understanding of the axioms, operations and properties for those students as well as new methods of conduct for teachers so that their work processes teaching become easier.